Analysis of Students’ Errors in Solving Social Arithmetic Word Problems in terms of the Learning Styles - Agus Indra Gunawan; Yuni Tri Astuti (Pusat Studi Pengembangan Pembelajaran Matematika Sekolah UIN Sunan Kalijaga Yogyakarta Jl. Marsda Adisucipto, Yogyakarta 55281, 2021)
Some abilities are needed to solve word problems, one of which is the ability to understand sentences and symbols in the problem. One factor that affects the ability of each student is learning style. Learning style is a person's tendency to receive and process information to the maximum, learning styles can be grouped into three, namely visual, auditory, and kinesthetic learning styles. The purpose of this study is to analyze and describe the forms of errors made by students in solving social arithmetic word problems in terms of the learning styles. Data collection procedures in this study are giving learning style questionnaire, written test, and interview. The research subjects are two VII grade students at SMP Negeri 1 Malang from each learning styles. The results of the analysis of this research are that students with visual learning style error occurs at the step of devising a plan, carriying out the plan, and looking back. While students with auditory and kinesthetic learning style error occurs at the understanding the problem, devising a plan, carriying out the plan, and looking back. The error forms occur in all learning styles.